Take your iPad to work - Proffitt, Brian (Boston : Course Technology, Cengage Learning, 2011)
The iPad has a robust application set with a large number of ways it can be used in business, but its potential as a business tool has been largely unexplored. This book discusses a range of business tasks, organized by general business type.--Books in Print
First step : introducing the iPad -- Second step : interfacing with the iPad -- Third step : connecting with the iPad -- Fourth step : using the iPad apps -- Work the web : Safari -- Get the word out : Mail -- Get to iWork : documenting with Pages -- Get to iWork : analyzing with Numbers -- Get to iWork : presenting with Keynote -- From iPad to paper : printing -- In the clouds : using MobileMe -- Remote desktop connectivity : LogMeIn ignition -- Ring me up : point of sale -- When the work's done : invoicing -- Shout to the world : social media -- Box it up : shipping -- Face-to-face, face-to-web : meetings -- Write online : web content creation -- Track online : web site management -- Make a list : task management -- See the big picture : project management -- Manage the customer : CRM -- From the home office : enterprise collaboration -- Get ready to go : travel arrangements -- On the plane : multimedia -- Continuing education : iBooks
Keywords: iPad (Computer) -- Handbooks, manuals, etc; Tablet computers -- Handbooks, manuals, etc; Business -- Data processing